2014
DOI: 10.1111/scs.12139
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle advice and lifestyle change: to what degree does lifestyle advice of healthcare professionals reach the population, focusing on gender, age and education?

Abstract: Health promotion practice in health care has a high priority in the endeavour to achieve equal opportunities for health and diversity in health among the population. The purpose of the study was to investigate whether there is any connection between the lifestyle advice given by healthcare professionals and the lifestyle change of the population, focusing on age, gender and education level. The study is based on the data from a national population survey in Sweden in which 52 595 patients who had attended heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 31 publications
5
21
2
1
Order By: Relevance
“…Gender is significantly associated with a healthy lifestyle. Compared to male, the female has a higher healthy lifestyle level, which is in line with the findings in [37]. The findings of this study support the report from earlier studies that a higher level of education may contribute to adopting a healthy lifestyle [37].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Gender is significantly associated with a healthy lifestyle. Compared to male, the female has a higher healthy lifestyle level, which is in line with the findings in [37]. The findings of this study support the report from earlier studies that a higher level of education may contribute to adopting a healthy lifestyle [37].…”
Section: Discussionsupporting
confidence: 92%
“…Compared to male, the female has a higher healthy lifestyle level, which is in line with the findings in [37]. The findings of this study support the report from earlier studies that a higher level of education may contribute to adopting a healthy lifestyle [37]. The age and healthy lifestyle have no significant association in the current research, which is in contrast to the previous findings where a negative correlation is between age and healthy lifestyle [38].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have highlighted the importance of identifying and addressing unmotivated sex differences in health care in general and patients’ complaints in particular . The present article has demonstrated the potential of the BN for understanding ‘gendered complaints’ in health care.…”
Section: Resultsmentioning
confidence: 66%
“…Indeed, in our population, women had a higher level of education compared to men and this could have affected the lifestyle of our patients. It is demonstrated that better educated people follow a healthier lifestyle, probably due to the increased awareness of the correlation between lifestyle and health (26).…”
Section: Discussionmentioning
confidence: 99%